Subclinical Thyrotoxicosis and Cardiovascular Risk: Assessment of Circulating Endothelial Progenitor Cells, Proangiogenic Cells, and Endothelial Function - Phowira, Jason; Bakhashab, Sherin; Doddaballapur, Anuradha; Weaver, Jolanta U. (Frontiers in Endocrinology, 2022)
Background: Subclinical thyrotoxicosis (SCT) is defined by low or undetectable thyroid stimulating hormone and normal thyroid hormones. The treatment of SCT is uncertain despite being associated with increased cardiovascular risk (CVR) and mortality. Circulating endothelial progenitor cells (cEPCs) and/or culture selected proangiogenic cells (PACs) have been found to be reduced in conditions with CVR. We aimed to evaluate whether endothelial function, cEPCs and circulating angiogenic cells (CACs) count were reduced in SCT and study in-vitro effect of tri-iodothyronine (T3) on PACs function from young healthy controls. Methods: CEPCs (quantified by flow cytometry, 20 SCT/20 controls), CACs following in-vitro cultures (15 SCT/14 controls), paracrine function of CACs, endothelial function by flow mediated dilation (FMD, 9 SCT/9 controls) and the effect of T3 on apoptosis and endothelial nitric oxide synthase (eNOS) expression in PACs were studied. Results: CEPCs count was significantly reduced in SCT compared to controls, median (range); CD34+ 1.1 (0.2-2.1) vs 2.3 (0.6-2.7), p < 0.001, CD133+/VEGFR-2+ 0.4 (0.0-0.7) vs. 0.6 (0.0-4.6), p=0.009, CD34+/VEGFR-2+ 0.3 (0.0-1.0) vs 0.7 (0.1-4.9) p=0.002; whilst CACs count was similar. SCT predicted lower cEPCs count after adjustment for conventional CVR factors. FMD was lower in SCT subjects, versus controls; (% mean ± SD, 2.7 ± 2.3 vs. 6.1 ± 2.3, p=0.005). In-vitro studies showed T3 increased early apoptosis and reduced eNOS expression in PACs. Conclusions: In conclusion, SCT is associated with reduced cEPCs count and FMD confirming increased CVR in SCT. Future outcome trials are required to examine if treatment of this subclinical hyperactive state improves cardiovascular outcome.